Genre et pronoms en anglais - Pierre Cotte (Anglophonia)
The grammatical category of gender, when it is ‘natural’, is a semantic property of linguistic units with independent grammatical functions. In this paper the gender of English pronouns is examined, with special emphasis on personal gender. It is argued that the nominal bases of the indefinite pronouns someone, somebody or something signify genders, not just categories. It is also argued that the interrogative pronouns who and what are subsequent to these pronouns logically. The paper finishes with some remarks about the affinities between personal gender and indefiniteness on one hand and sex-based gender and definiteness on the other. These point to a single encompassing system of gender and nominal determination.